The Threat of Urban Warfare in Jayapura Region: A Case Study of Expulsion of Muslim Residents in Papua - Widodo, Pujo; Somantri, Gumilar Rusliwa; Ghafur, A. Hanief Saha (Journal of Governance, 2024)
The rebellion by a small number of Papuans using the strategy of expelling immigrants under the pretext of discrimination in the Surabaya case created ethnic Papuan conflict with migrants (Muslims) and threatened the city of Jayapura, which was an asymmetric urban war. The purpose of this research is to create a strategy for counteracting the threat of urban warfare in the Jayapura region of Indonesia. This research method is qualitative in nature with a case study approach supported by conflict root data, threat data, and ethnic Papuan discrimination data against migrants. The results of this study are, first, the threat of urban warfare in the Jayapura region in the form of horizontal conflicts expelling immigrants and killing Muslims. Second, the implementation of the Papua provincial government's handling of building reconstruction, infrastructure paid for by Papuans, and ensuring the safety of migrant residents. Third, the strategy of counteracting the threat of urban warfare by increasing territorial operations supported by combat operations, intelligence, and security and order. The conclusion of this study is that the expulsion of Muslim residents in Papua was caused by the desire of some separatist groups supported by foreigners to carry out demonstrations in the cities of Papua province.